1955
DOI: 10.1037/h0043004
|View full text |Cite
|
Sign up to set email alerts
|

The effect of adrenocorticotrophic hormone (ACTH) on avoidance conditioning in the rat.

Abstract: The various changes in mood and behavior that may occur in patients treated with adrenocorticotrophic hormone (1,6) have made it pertinent to assess the effect of exogenous ACTH on behavior motivated by noxious stimulation. That some effect of ACTH on avoidance conditioning does occur is revealed in studies discussed by Mirsky, Miller, and Stein (5).In avoidance conditioning the animal must respond appropriately to the conditioned stimulus in order to prevent the occurrence of the painful unconditioned stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
40
1

Year Published

1957
1957
1996
1996

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(42 citation statements)
references
References 4 publications
1
40
1
Order By: Relevance
“…The increased resistance to extinction of avoidance responding found in hippocampal animals (Isaacson et al, 1961) has also been demonstrated in ACTH-injected animals (Murphy & Miller, 1955). The deficit in spontaneous alternation that has been observed in hippocampally lesioned animals (Roberts, Dember, & Brodwick, 1962) has been replicated via elevation of ACTH as well (File, 1978).…”
mentioning
confidence: 51%
“…The increased resistance to extinction of avoidance responding found in hippocampal animals (Isaacson et al, 1961) has also been demonstrated in ACTH-injected animals (Murphy & Miller, 1955). The deficit in spontaneous alternation that has been observed in hippocampally lesioned animals (Roberts, Dember, & Brodwick, 1962) has been replicated via elevation of ACTH as well (File, 1978).…”
mentioning
confidence: 51%
“…Murphy and Miller (1955) reported that exogenous ACTH served to prolong the conditioned avoidance responding (CAR) of rats in the two-way shuttlebox during extinction. Later, essentially the same finding was reported with adrenalectomized rats (Miller & Ogawa, 1962).…”
mentioning
confidence: 99%
“…Animals studied include the rat (Murphy & Miller, 1955), cat (Endroczi & Lissak, 1962), mouse (Koranyi et al, 1967), rabbit (Bertolini et al, 1969), dog (Ferreri et al, 1963), monkey (Mirsky et ai, 1953), and man (Cleghorn, 1952). Some of the behaviors include: sexual behavior (Bertolini et aI, 1969), the "stretching syndrome" (Ferrari et al, 1963), active avoidance (Murphy & Miller, 1955), passive avoidance (Weiss et al, 1969), and CER (Levine & Jones, 1965).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Since Sheffield and Temmer (1950) have suggested that an avoidance response persists for an unusually long time in comparison with other type of conditioning (escape response), Murphy and Miller (1955) developed the method to establish a high degree avoidance response which was resistant to extinction. Many authors, Fellows and Cook (1957), Cook and Weidley (1957), Miller et al (1957), Irwin et al (1959Irwin et al ( , 1961, , and others observed the suppression of conditioned avoidance behavior by use of phenothiazine tranquilizers effective in the treatment of psychoses.…”
mentioning
confidence: 99%